Myocardial Infarction in Non-obstructive Coronary Arteries (MINOCA) in the Perioperative Period can Epinephrine be Responsible? - Koirala, M.; Shakya, B. M.; Parajuli, B.; Ghimire, B. (Kathmandu University Medical Journal, 2022)
Ephedrine, metaraminol, epinephrine and maneuvers like carotid sinus stimulation used during intraoperative period have been postulated to cause temporary spasm of the coronary vessels leading to decrease supply to the myocardium and precipitating myocardial infraction in non-obstructive coronary arteries (MINOCA). As an anaesthesiologists, we should be aware that even a dose as small as 25 mcg epinephrine infiltrated along with local anaesthetic in the subcutaneous plane may be responsible for coronary vessel spasm and thus myocardial infraction in nonobstructive coronary arteries. We report a case of 45 years old female with papillary carcinoma of thyroid who developed features of non-ST elevation myocardial infarction 5 minutes after the subcutaneous infiltration of 5 ml of 2% Xylocaine with 1:200000 Epinephrine. Patient was managed for acute Myocardial Infarction. Coronary angiogram done the next day revealed normal coronary arteries, hence the diagnosis Myocardial infraction in non-obstructive coronary arteries was made.